Zeros of irreducible characters of prime power degree - Mahmood Robati, Sajjad; Hafezieh, Roghayeh (Taylor & Francis Inc, 2025)
Let G be a finite group. An element x is an element of G is called a vanishing element if it is a zero of an irreducible character of G. In this paper, we characterize those finite Fitting-free groups whose nonlinear irreducible characters of prime power degree vanishes on at most three conjugacy classes.
Keywords: Finite groups; irreducible character; prime power degree; vanishing element